Rozkaz No 1. = Prikaz No 1. = No 1 lh'p'b. ([S.l. : s.n.], 1920)
Afisz z tekstem rozkazu z 12.08.1920 r.
Tekst równol. w jęz. pol., ros. i yid.
Keywords: Wojna polsko-bolszewicka (1919-1920) -- druki ulotne